Thoracoscopic diagnosis and repair of central congenital diaphragmatic hernia in a neonate: A case report of a rare entity - Mario Lima; Raed Al-Taher; Tommaso Gargano; Michela Maffi (Journal of Pediatric Surgery Case Reports, 2017)
Introduction: Central congenital diaphragmatic hernia that involves a central tendon defect is a very rare form of diaphragmatic hernias. Experience in the thoracoscopic repair of congenital diaphragmatic hernia has expanded in recent years, but this expansion was mainly for the most common type; the posterolateral. We report a case of central congenital diaphragmatic hernia, which is supposed to be the case number seventeen of those reported in literature. And we report the first use of thoracoscopic repair in such rare entity. Case presentation: We present a case report of a Bengali neonate who had a prenatal diagnosis of left congenital diaphragmatic hernia, which was supposed to be the usual posterolateral type. As we usually approach such cases by thoracoscopy, the patient had an intraoperative diagnosis of central congenital diaphragmatic hernia. The defect was amenable to a successful thoracoscopic repair. Conclusion: The rare neonatal central congenital diaphragmatic hernia could present as a left sided herniation that clinically resembles the usual posterolateral congenital diaphragmatic hernia. Thoracoscopic approach offers a tremendous tool for diagnosis as well as the management of this kind of presentation of a central congenital diaphragmatic hernia.